Case report: A rare case of breast and multiorgan metastases secondary to papillary thyroid carcinoma - Huang, Wenqin; Yang, Yalong; Zhan, Peng; Jiang, Liang; Chen, Jian; Zheng, Hongmei (Frontiers in Oncology, 2024)
Papillary thyroid carcinoma (PTC) is generally considered a highly indolent endocrine malignancy, often accompanied by cervical lymph node metastasis and rarely involving distant metastases. We present a rare case of a 37-year-old woman with PTC, who exhibited regional lymph node metastasis, right breast metastasis, and probable right psoas major and multiple bone metastases. Initial symptoms included hoarseness, and subsequent examination revealed a secondary malignant tumor in the right breast, originating from the thyroid gland. This case highlights an unusual pattern of multiple systemic metastasis in PTC, particularly the rare occurrence of breast metastasis.